PENGEMBANGAN KESADARAN SEJARAH SISWA DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR DENGAN MEDIA FILM - Siska, Yulia; Suryati, Wawat (STKIP PGRI Bandar Lampung, 2020)
This paper focuses on developing students' historical awareness in history learning in high school through the inquiry method. The purpose of this study was to identify the development of students' historical awareness through film media with the theme of Indonesian history. Data obtained through books, journals, theses, proceedings, and websites related to the object of research were then analyzed using text analysis techniques. The results showed that film media was very helpful in making history learning more interesting, showing students that the facts exist and also providing opportunities for students to actively participate in history learning and encouraging students to be active in responding to questions and problems and drawing their own conclusions: critical thinking, logically, critically, and systematically so that historical awareness grows stronger.